Non COVID Symptoms and its Impact on Quality of Life among the Professionals Residing at Pune City - Sharadha Ramesh1 , Poonam Yadav2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: COVID-19 has made all of us understandably too much cautious to visit the physician’s.We have rescheduled the appointments and trying to manage our care viva virtual visits, Also trying tostay safe by restricting movements. It’s important to keep taking precautions like handwashing, avoidtouching face area and also wearing the masks in public. Hence it’s very important for all of us to knowwhen to seek medical help.Objectives of the study: 1.To assess the Non COVID Symptoms among working professionals in PuneCity 2.To assess the impact of Non Covid symptoms on quality of life among working professionals inPune City 3.To associate the selected Demographic variable with the Non COVID Symptoms amongworking professionals in Pune CityMethodology: Survey study was conducted among 265 working professionals in Pune City. Nonprobability convenience sampling technique was used to select the samples. Informed consent was obtainedfrom all participants, and made them aware that the information gathered is used only for research purpose.Structured questionnaires were prepared to elicit information from the participants.Result: The study result says that are various Non Covid symptoms which the general population is facingin the current scenario which are being identified in the study result and also the Non Covid symptoms arebeing associated with the various selected demographic variable the result pertaining to that shows thatthere is significant association between working profession and monthly family income with Non COVIDSymptoms as the P value is less than 0.05.In this current situation the investigator wanted to recommendedfurther studies to find out the various other Non covid symptoms faced by the general population an shouldbe paid attention and treated on time.